Ecocardiografía en clínicas veterinarias de pequeños animales: Informe práctico para los estudiantes en fase de pasantía profesional - Conrado, André Luiz Veiga; Corredor-Castillo, Adriana Soliris [UNESP]; Cardoso, Fernanda; Ramos, Cristiane Cagnoni; Bruno, Carlos Eduardo Malavasi (My University, 2016)
Echocardiography is the study of the different cardiac structures through the use of ultrasonic beams and this is a recent area of veterinary diagnostic imaging. It is a tool used for diagnostic evaluation and appropriate management of dogs and cats with suspected congenital and acquired heart disease. The operation of the transducers is based on piezoelectric effect whereby sound waves between 2 and 7 MHz are created, and the transducers are setted up in specific places of the thorax for image acquisition. There are different types of echocardiography as the M-mode, the two-dimensional echocardiography and the Doppler echocardiography, which is constituted by continuous wave Doppler, pulsed wave Doppler and Doppler color flow. For the echocardiographic examination, most dogs and cats are setted up in right lateral recumbent position and the exam may last between 45-60 minutes. With the use of various Doppler modalities, the images obtained from different planes of various cuts. Thus, it is possible to estimate the relationship among the structures and mainly for the left ventricle, it is possible to calculate its volume and mass, end-systolic volume and ejection fraction, its fractional shortening of myocardial fiber and its velocity of circumferential fiber shortening. It is expected that students and apprentices in the area of veterinary diagnostic imaging, especially echocardiography, may have this material as a basis for their studies.
Echocardiography in small animal veterinary clinics: Practical report for students undergoing professional internship
Keywords: Doppler; Echocardiography; Internship